1999
DOI: 10.1002/(sici)1097-4636(199901)44:1<78::aid-jbm9>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of calcium phosphate ceramics

Abstract: Degradation of three types of sintered calcium phosphate ceramic spheres was investigated in vitro at low pH conditions (LPC) and in an in vivo model, that is, injection into a mouse peritoneal cavity. Degradation was observed under both conditions. The rate of degradation depended on the type of ceramic, with beta-TCP degrading faster than HA and HA degrading faster than FA. Degradation was characterized by dissolution of the necks and the formation of cracks and irregularities in the grains. Intraperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 15 publications
(15 reference statements)
6
85
0
1
Order By: Relevance
“…Recent "ndings that osteoblasts phagocytosed Ti particles [29] and osteoblasts treated with cytochalasin-D (agent that inhibits phagocytosis by affecting actin "lament assembly of the cytoskeleton) almost completely suppressed the negative e!ect of Ti particle on osteoblast viability [17] supports this hypothesis. As for the macrophages or multinucleated giant cells [19], this phagocytosis process could produce an accumulation of calcium in mitochondria and could eventually lead to lysis of mitochondria and cell death. Impact of CPC particles on osteoblast functions could Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent "ndings that osteoblasts phagocytosed Ti particles [29] and osteoblasts treated with cytochalasin-D (agent that inhibits phagocytosis by affecting actin "lament assembly of the cytoskeleton) almost completely suppressed the negative e!ect of Ti particle on osteoblast viability [17] supports this hypothesis. As for the macrophages or multinucleated giant cells [19], this phagocytosis process could produce an accumulation of calcium in mitochondria and could eventually lead to lysis of mitochondria and cell death. Impact of CPC particles on osteoblast functions could Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been performed with CPC particles smaller than 10 m. An in vivo study using mice has shown that CPC particles of around 10 m could be degraded by macrophages or multinucleated giant cells [19]. This degradation process produced an accumulation of calcium in mitochondria and "nally led to lysis of mitochondria and cell death [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, dissolution-precipitation reactions that are involved during calcium phosphate resorption (LeGeros, 1993;Koerten and van der Meulen, 1999;LeGeros, 2002;Le Nihouannen et al, 2005) were seen to occur between partly dissolved grains ( Van der Meulen and Koerten, 1994). LeGeros et al (LeGeros et al, 1988) and Klein et al (Klein et al, 1983;Klein et al, 1986) observed an increase in resorption rate with a decrease in grain size.…”
Section: No Differencementioning
confidence: 99%
“…the sealing zone) that delimits the resorbing area onto which osteoclasts generate an acid milieu that can reach values below pH 3, resulting in the dissolution of the underlying mineral [36]. In this regards, studies performed at low pH can be used as predictors of osteoclastic degradation [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%